A Study On Peer Response InWriting Class In English Department Of MuhammadiyahUniversity Of Surakarta In 2013/2014 Academic Year. - Nuriyanti, Nurul; , Mauly Halwat Hikmat, Ph. D; , Nur Hidayat, M.Pd (2015)
The research paper aims at finding out and describing peer response in writing class in EnglishDepartment of Muhammadiyah University of Surakarta. The type of this research is case study. The subjects of this research are ten students of a writing class as the sample for the research. The methods of collecting data are observation, interview, and document analysis. The result of this research shows that ten students in writing subject use almost all the peer response proposed by Nelsom and Murphy. However their responsesare different. The researcher finds the correction can be classified into four categories. They are; unnecessary correction(4%), accurate correction(46%), inaccurate correction (19%), and disregard (31%) from 48 data at students' response to their friend's work. The researcher divided two categories in students' response to the correction. They are; students revising the sentences and students disrgarding thee correction. The last finding, the researcher found that most of the students 60% perceive that peer rsponse gives bnefits; grammatical and structural. Peer respons can be used as one stratgy of teaching writing as proposd by Nelsom and Murphy.